Dragonheart [videorecording (DVD)] : vengeance - Silvestrini, Ivan; Millson, Joseph; Kane, Jack, 1999-; Muselli, Arturo (Universal Pictures Home Entertainment, 2020)
When a young man's family is killed by marauders, he seeks the help of a swashbuckling mercenary and a reclusive dragon in a quest for vengeance. The unlikely trio's adventurous journey brings revelations and rewards far beyond the original intent.